Writing research papers : a complete guide - Lester, James D. , 1935-2006; Lester, James D. , 1935-2006 (Pearson, 2012)
This text provides readers with step-by-step guidance through the research writing process, from selecting and narrowing a topic to formatting the finished document. Writing Research Papers backs up its instruction with the most complete array of samples of any writing guide of this nature. The text continues its extremely thorough and accurate coverage of citation styles for a wide variety of disciplines